2021
DOI: 10.3856/vol49-issue2-fulltext-2660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein: lipid ratio on growth, feed efficiency, and metabolic response in juvenile yellowtail snapper Ocyurus chrysurus (Bloch, 1791)

Abstract: This study was conducted to evaluate juveniles' Ocyurus chrysurus (13.7 ± 0.45 g initial weight) to utilize lipid as an energy source on growth, feed efficiency, body composition, digestive and hepatic enzyme activities. Four diets of two protein levels (40 and 50%) with two lipid levels (6 and 12%) and 2% of digestible carbohydrates were formulated. Fish were fed for 60 days to apparent satiation at a stocking density of 10 fish per tank (100 L). Growth gain of fish fed 50% dietary protein was higher than of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The FCR of both treatments coincides with that described by Arenas et al (2021) for the evaluation of different diets for juvenile stages (13.7 ± 0.45 g) in yellowtail snapper. For the same species reared in cages, an FCR of 1.35 was obtained without considering the humidity of the feed; otherwise, it would be 4.54 (García Torcuato et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The FCR of both treatments coincides with that described by Arenas et al (2021) for the evaluation of different diets for juvenile stages (13.7 ± 0.45 g) in yellowtail snapper. For the same species reared in cages, an FCR of 1.35 was obtained without considering the humidity of the feed; otherwise, it would be 4.54 (García Torcuato et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Another reason is the relation between the amount of protein and lipids in the food and protein the organism can assimilate. Arenas et al (2021) obtained the best growth results with high protein and lipid levels (50% and 12% respectively) in juvenile stages. Although the diet of yellowtail snapper is based on penaeid crustaceans (Rinc on-Sandoval et al, 2009), is possible that the amount of protein in the diet was higher than the requirements of the organisms at this size.…”
Section: Welfare Of O Chrysurus In Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Enríquez et al (2017) reported better growth performance in juvenile Yellowtail Snapper that received protein at a rate of 50 g/kg of diet. Furthermore, Arenas et al (2021aArenas et al ( , 2021b investigated the effect of increasing dietary lipid content on the growth of Yellowtail Snapper. They found that the feed efficiency of this species improved when the lipid content increased from 60 to 120 g/kg.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the feed efficiency of this species improved when the lipid content increased from 60 to 120 g/kg. In addition, Arenas et al (2021aArenas et al ( , 2021b reported that Yellowtail Snapper had a low ability to use digestible carbohydrates as energy substrates. It is important to note that specific growth rates for Yellowtail Snapper were reported in these studies; Arenas et al (2021aArenas et al ( , 2021b reported a specific growth rate of 1.26% per day, while Enríquez et al (2017) reported a specific growth rate of 1.01% per day.…”
Section: Introductionmentioning
confidence: 99%